Keadilan Substantif dan Transformasi Hukum Pidana: Pendekatan Filsafat Hukum Alam - Ibnu Asa, Agam; Mukhtasar Syamsuddin , Muhammad (Jurnal Hukum Ekualitas, 2026)
This study explores the application of substantive justice principles in Indonesia’s criminal justice system through the lens of natural law philosophy. Natural law demands a paradigm shift from rigid legal formalism toward an approach that emphasizes moral, humanitarian, and contextual justice values. Within this framework, law is not merely seen as a set of written rules, but as an expression of universal moral principles derived from human reason. The thoughts of philosophers such as John Rawls, Aristotle, and Jeremy Bentham reinforce the urgency of substantive justice, particularly in protecting vulnerable groups, restoring social balance, and achieving public benefit. This research employs a qualitative method with juridical and philosophical approaches, focusing on analyzing the role of law enforcement officials in implementing substantive justice through criminal sentencing. The findings reveal that the prevailing legalistic approach hinders the realization of substantive justice. Major obstacles include unequal access to justice, low integrity among law enforcers, and the dominance of retributive punishment. Although restorative justice practices are beginning to emerge, their implementation remains limited and inconsistent. The study recommends strengthening legal aid for vulnerable groups, internalizing ethical values in legal education and training, and developing policies aligned with substantive justice principles. Collaboration between the state, civil society, and academia is essential to building a criminal justice system that is not only repressive but also transformative and capable of serving as a means of social restoration that upholds human dignity.